Penyatuan Pembinaan Pengadilan Pajak - Budi Ispriyarso (Administrative Law and Governance Journal, 2019)
AbstractTax Courts in Indonesia based on Law Number 14 of 2002 concerning Tax Courts. Tax Court contains many weaknesses. One of its weaknesses is the dualism of building the Tax Court, namely the Ministry of Finance and the Supreme Court. This dualism of formation must be eliminated. The problem is how to eliminate the dualism of coaching. The dualism of coaching the Tax Court can be removed by uniting the coaching of the Tax Court in both the technical coaching of the judiciary and the coaching of the organization, administration, and finance under the Supreme Court. The dualism provisions of coaching the tax court in the Tax Court Law must be immediately amended. Keywords: Coaching Dualism, Tax Court, Integration. AbstrakPengadilan Pajak di Indonesia berdasarkan Undang-undang Nomor 14 Tahun 2002 tentang Pengadilan Pajak. Pengadilan Pajak, banyak mengandung kelemahan. Salah satu kelemahannya adalah adanya dualisme pembinaan Pengadilan Pajak, yaitu oleh Kementerian Keuangan dan Mahkamah Agung. Dualisme pembinaan ini harus dihilangkan. Permasahannya adalah bagaimana cara menghilangkan dualisme pembinaan tersebut. Dualisme pembinaan Pengadilan Pajak, dapat dihilangkan dengan cara menyatukan pembinaan Pengadilan Pajak baik pembinaan teknis peradilan maupun pembinaan organisasi, administrasi dan keuangan di bawah Mahkamah Agung. Ketentuan dualisme pembinaan pengadilan pajak dalam UU Pengadilan Pajak harus segera diubah. Kata Kunci : Dualisme Pembinaan, Pengadilan Pajak, Penyatuan.